Approaching an Unclosed Whole1 through a Triadic Analysis of The Love Song of J. Alfred Prufrock - Ahsan, Md. Firoz Mahmud; Huq, ABM Monirul (Stamford Journal of English, 2013)
Any message encoded in a certain discourse on the common ground of reference, purpose or aim that a discourse serves, runs the risk of semantic gap at the crucial moment of decoding. The response(s) may contradict the feedback, or else the feedback may bring about epistemic violence and thereby may subvert the projected meaning(s). Teaching T.S. Eliots poem, The Love Song of J. Alfred Prufrock as a part of an undergraduate course at a University (in Bangladeshi context) led us to the discovery of a threefold analysis (phase by phase) of the poem: a. constituent analysis, b. structuralist reading, and c. dialogic criticism, which was quite challenging. This paper aims at analysing the stated poetic piece as a discourse and setting it against the backdrop of a literature classroom at the tertiary level with a view to understanding how the aforementioned three-phase-analysis of a text can help the learners go beyond the limit of identifying with the objective reading of a discourse, and thus they pave their way to the undiscovered world of signification and eventually can relate to a social context where the meaning is multiple and the voices are polyphonic. Stamford Journal of English; Volume 6; Page 27-40 DOI: http://dx.doi.org/10.3329/sje.v6i0.13900